Pengaruh Laju Pertumbuhan Sektor Industri, Investasi Dan Upah Terhadap Penyerapan Tenaga Kerja Sektor Industri Di Provinsi Banten Tahun 2011-2020 - Gerry Cahya Mutaqin; Ima Amaliah (UNISBA Press, 2023)
Abstract. The manufacturing industry sector is a buffer for economic growth in Banten Province with an average contribution of 5% per year. However, on the other hand, Banten Province is the province with the highest unemployment rate in Java, which is 10%. In 2020 the unemployment rate in Banten Province will reach an average of 10%. This study aims to determine the effect of the growth rate of the industrial sector, investment and wages on employment in the industrial sector in Banten Province in 2011-2020, and to determine how much influence the growth rate of the industrial sector, investment, wages and employment of the industrial sector in the Province Banten in 2011-2020.This study uses a quantitative descriptive analysis approach and regression analysis using OLS with annual time series data for the 2011-2020 period. Data obtained from the Central Bureau of Statistics. The independent variables include the growth rate of the industrial sector, investment, and wages and the dependent variable, namely employment in the industrial sector. From the estimation results of the model, the industry growth rate, investment and wages partially affect the absorption of labor in the industrial sector in Banten Province. However, the direction of the LPI relationship is not in accordance with the hypothesis, namely the LPI relationship with the industry growth rate is negative. The negative relationship between LPI and employment is due to technological developments and automation in the industry. Increasing the use of machines and production technology can reduce dependence on human labor so that labor absorption becomes lower. Abstrak. Sektor industry pengolahan merupakan suatu penyangga pertumbuhan ekonomi di Provinsi Banten dengan kontribusi rata-rata 5% pertahun. Namun disisi lain Provinsi Banten merupakan provinsi dengan tingkat pengangguran tetinggi di Pulau Jawa yaitu sebesar 10%. Pada tahun 2020 tingkat pengangguran di Provinsi Banten mencapai rata-rata 10 %. Penelitian ini bertujuan untuk mengetahui pengaruh laju pertumbuhan sektor industri, investasi dan upah terhadap peyerapan tenaga kerja sektor industri di Provinsi Banten tahun 2011-2020, serta untuk mengetahui berapa besar pengaruh laju pertumbuhan sektor industri, investasi, upah dan penyerapan tenaga kerja sektor industri di Provinsi Banten tahun 2011-2020. Penelitian ini menggunakan metode pendekatan analisis deskriptif kuantitatif dan analisis regresi menggunakan OLS dengan data time series tahunan periode 2011-2020. Data diperoleh dari Badan Pusat Stastistik. Variabel independen meliputi laju pertumbuhan sektor industri, investasi, dan upah serta variabel dependennya yaitu penyerapan tenaga kerja sektor industri. Dari hasil estimasi model, laju pertumbuhan industry, investasi dan upah secara parsial berpengaruh terhadap penyerapan tenaga kerja sektor industry di Provinsi Banten. Namun arah hubungan LPI tidak sesuai dengan hipotesis yaitu hubungan LPI dengan laju pertumbuhan industry negative. Negative hubungan LPI dengan penyerapan tenaga kerja dikarenakan adanya perkembangan teknologi dan otomatisasi dalam industry. Peningkatan penggunaan mesin dan teknologi produksi dapat mengurangi ketergantungan pada tenaga kerja manusia sehingga penyerapan tenaga kerja menjadi lebih rendah. Kata Kunci: Laju Pertumbuhan Sektor Industri, Investasi, Upah, Penyerapan Tenaga Kerja Sektor Industri